11 - Le plan d'action de Lagos et les femmes - Marie Angélique Savane, (Africa Development, 1982)
As part of the integration of women into the African development process, the Lagos Plan of Action recommends number of actions in the areas of education, employment, health, nutrition, communication, research etc... in order to make a better use of women's skills. In this article, the author wants to show that the concept on which these proposals of actions are based does not allow the proper apprehension o the mechanisms through which women contribute to the national economy and that such proposals cannot henceforth materialize within the framework of the present development strategies. After a brief introduction in which she sums up women's contribution to the African development frocess to demonstrate that despite their decisive roles both in the national economy and in the family, women still have a lower status in the society in which they are the victims of exploitation and/or oppression, the author analyses the conceptual approach of the LPA. Such and approach, in the author's view, is essentially characterized by an «idealism» which completely ignores the dialectical link between women's problems and society. Thus the recommendations seem to regard women as an entity without any interacti.on with the other members of society and the solution to their problems can be envisaged isolatedly and independently. In conclusion, the author expresses the view that the IPA neither raises the point of women's yoke in the measures advocated to solve the issue of women's employment nor does it do so in the administrative and legislative actions taken recently in the various African countrie. Now, as far as the author is concerned, it is practically impossible to change women's living conditions without questioning once again their cultural justificati.ons. Therefore the chapter devoted to women only reinforces the ghetto status usually given to women's problems. A conceptual effort shoula be made to include women's specific problems in the analysis of the African economic situation. Only thus can women's cause be effectively heard. Marie Angélique Savane, Présidente de l'Association des Femmes Africaines pour la Recherche sur le Développement ( AFARD ) -B.P. 3 1 86, Telex : 5 79 IDEP (Dakar)